Sistem Pendukung Keputusan Menentukan Indukan Bandeng Menggunakan Metode SAW - Rudi Hariyanto (Universitas Muhammadiyah Sidoarjo, 2017)
Abstract Breeding fish diseases are undesirable for fish farmers, because it can cause not maximal harvest in fish. To overcome these obstacles then the farmers need a knowledge of disease information, symptoms, and handling for the disease to be a good parent. But the availability of information about fish diseases this causes difficulties in the handling and the way of treatment. Implementation of expert system with SAW method in determining the quality of milkfish to become one of solution / alternative.